The effectiveness of Proteolytic bacteria isolated from effluent of Modjo tannery for their application in the leather and detergent industry - Tayachew Desalegn; Ketema Bacha; MesfinTafesse; chandran masi (Kuwait Journal of Science)
Protease also called proteinase or peptidase is a digestive enzyme that is categorized under Proteolytic enzymes and it has great potential in industrial application. Extracellular proteases have many applications in different industries because they have almost every feature desired for their biotech applications such as detergent, bioremediation, food, and leather processing industries. In the synthesis of all three major types of acidic, neutral, and alkaline proteases, microbial sources have dominated an unbeatable area. Alkaline proteases are a large group of industrial enzymes formed by a wide variety of species, including animals, fungi, and bacteria. The fermentation method serves to make bacteria, fungi, and yeast alkaline proteases. Proteases are produced in large quantities by Gram-positive bacteria, especially those belonging to the Bacillus genus. Following standard procedures, the bacterial isolates (PMOJ-01 and PMOJ-05) with the prominent zone of clearance and efficient enzyme development were further characterized to the genus level. Moreover, the growth conditions for the highest protease production were optimized with different pH, temperature, and NaCl concentration. The proteases from PMOJ-01 (Pseudomonas aeroginosa sp.) and PMOJ-05 (Bacillus subtillis sp.) were active at pH 7.5 to pH 8.0 and temperature of 35oC to 37oC, respectively. The enzyme activity and the total solid protease sample of the crude enzyme of PMOJ-01 (Pseudomonas aeroginosa sp.) and PMOJ-05 (Bacillus subtillis sp.) were 0.299 U/ml and 0.289 U/ml, 1.37 U/mg, and 1.199 U/mg respectively. The effect on dehairing, distaining, and scum removal revealed that the purified protease enzyme of PMOJ-01 and PMOJ-05 can be used in detergent and leather industries.